Antibiotic Susceptibility Patterns of Bacterial Strains Isolated From Skin Samples of Healthy Individuals - Smyrna, Moti Rawanan Shah (2018)
Antibiotics resistant pathogens are becoming a more serious global threat. Due to natural selection. bacterial strains have developed resistance towards antibiotics and this has resulted in an increase in hospitalization, death and cost as the antibiotics are less effective towards these bacteria. This is why it is important to determine the antibiotic susceptibility pattern of bacterial strains to know which antibiotics can still be used to treat infections. The aims of this study were to isolate and identify bacterial strains from facial samples collect from individuals in INTI International University and to determine the antibiotic susceptibility profiles of these bacteria. The samples were incubated in nutrient broth which were further cultured on nutrient agar. Single colonies were picked and were subjected to biochemical test such as Gram staining, catalse test, Mannitol Salth Agar, blood agar, MacConkey agar, IMViC Tests, Triple Sugar Iron, Citrate test, Brilliance MRSA 2 agar and disk-diffusion assay. 49 isolates were obtained from the 30 samples collected. 98% were gram positive while 2% were gram negative bacteria. There was a higher percentage of Staphylococcus aureus (51%) while Staphylococcus epidermidis (15%). Enterococcus species (12%). Propionibacterium acnes (10%) and Streptococcus pneumoniae (2%) . 10% of the bacteria could not be identified. The single S, pneumoniae was identified to bePRSP since it was resistant to penicilin. 18% and 6% were identified to be MRSA and MRSE respectively. All the MRSA strains were resistant to cefoxitin, ampicillin G while all the MRSE strains were resistant to cefoxitin and ampicillin. There were five different antibiograms for the MRSA and only two antibiograms for MRSE strains. 40% of the P.acnes were resistant to erythromycin. From the study 5% of the isolate were not sensitive to the antibiotics while 95% were resistant to at least one anti biotic. The reslts obrained from this study allows the determination if the antibiotic resistant bacteria are increasing in Malaysia and it also enables the determination of which antibiotic can still be used to treat infections caused by bacteria.